Student Engagement and Learning Success: Evidence from Hybrid and Online Classrooms - Vergara, Kimberly Christie S.; Vergara, Raymond Allan; Trinidad, Loren Aina L. (Future Science / FSH-PH Publications, 2026)
This inquiry is the second phase of a teacher-led initiative that began in 2020 to examine the relationship between student engagement and learning success in the undergraduate classroom. Whereas the initial phase examined engagement and success in the online classroom, this study extends the inquiry to explore engagement and success in the hybrid classroom. Using a convergent mixed methods approach involving 575 students from different cohorts across 6 years, this study finds that there is a significant and positive relationship between student engagement and learning success. Specifically, engagement and active participation serve as a pathway to learning success through opportunities that enable knowledge development, knowledge application, and skill development.